Freiburg personality inventory fpi – validity testing and local standardization - Луценко, Олена Львівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2017)
The article highlights the results of checking the validity and local standardization of the multidimensional test – Freiburg Personality Inventory – in conditions of Eastern Ukraine (Kharkiv region and Kharkiv). The problem of the study is that this method has been adapted and standardized in St. Petersburg at the end of the twentieth century, on a sample of young adults. The purpose of the research is to check the validity and to find local norms for test in modern conditions on a sample of middle-aged and elderly people. Validation has been done by R. Lazarus Coping Test, psychophysiological method of heart rate variability analysis and age / sex differentiation. Standardization was conducted on a sample of 335 persons of 30-63 years old. The study proved the validity of the test. It was calculated the norms in stanine-scale.